ANALISIS TATANIAGA KOPI ARABICA (COFFEA ARABICA L) DESA MEREK, KECAMATAN MEREK, KABUPATEN KAROSUMATERA UTARA TAHUN 2019 - Dippu Pasaribu; Robert G. Marpaung; Jenni A Mendrofa (Jurnal Darma Agung, 2021)
This study aims at determining the channels, functions and institutions of the Arabica coffee trading system in the research area, the margin of the trading system produced by the Arabica coffee (coffeaarabica L) in the study area, the efficiency level of the Arabica coffee trading system (Coffeaarabika. in the research area. The research area was determined by purposive sampling in Brand Village, Merek District, Karo Regency which was held in May 2019 - August 2019. The sampling method was carried out by simple random sampling (simple random). The samples in this study are farmers who cultivated Arabica coffee throughout the year. The number of samples in this study was 30 samples and the sample of traders was determined by the tracing method, namely tracing all traders involved in the Arabica coffee trading process. There are two marketing channels for Arabica coffee in the research area, namely farmers - collecting traders - subdistrict traders and subdistrict farmers - traders. The marketing margin for Arabica coffee from farmers to consumers on channel I is Rp. 14,500, on channel II is Rp. 14,300. The coffee marketing channels in Brand Village, Brand District, Karo Regency are efficient. Of the two marketing channels, the most efficient marketing channel compared to other marketing channels is the second marketing channel, namely sub-district farmers - traders.